The Imagination of Singapore's Smart Nation as Digital Infrastructure: Rendering (Digital) Work Invisible. Issue 4 (1st December 2019) - Willems, Thijs; Graham, Connor
Abstract: This article aims to understand contemporary forms of "digital work" and how this is imagined in visionary documents in the context of smart urbanism. Specifically, we argue for an infrastructural perspective on smart urbanism to highlight (1) how such visionary documents organize society in specific ways and (2) how this organization is rooted in work that is imagined as being mainly informational and disembodied. Through an analysis of Singapore's recent Smart Nation initiative, we make a case for the inclusion of the actual human and embodied work that constitutes visions of smart urbanism. This work comprises both the physical construction and maintenance of digital infrastructure and the monitoring of these infrastructures and the interpretation of data on which they run. Finally, we show how an infrastructural inversion of smart urban initiatives is capable of highlighting these invisibilities of human work, specifically by drawing on the mundanity, temporality, and materiality of work that is considered digital.